2001
DOI: 10.1128/jcm.39.11.3842-3850.2001
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Growth and Urease Detection in the Chemically Defined Medium Ham's F-12 Nutrient Mixture

Abstract: Obstacles continue to hinder in vitro studies of the gastric human pathogen Helicobacter pylori, including difficulty culturing the organism in the absence of serum or blood, rapid loss of viability following exponential growth due to autolysis, and the necessity for using high starting inocula. We demonstrate that H. pylori grows in the chemically defined broth medium Ham's F-12 nutrient mixture (F-12) in the absence of fetal bovine serum (FBS); this represents a breakthrough for studies in which serum compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
106
2
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(115 citation statements)
references
References 33 publications
6
106
2
1
Order By: Relevance
“…Brucella broth supported some motility, but a large number of cells were observed to swim only when FBS was present. FBS is known to promote robust H. pylori growth (Testerman et al, 2001), but our data show that it also promotes motility. For this reason, we used FBScontaining medium (BB10) for all further analyses.…”
Section: H Pylori Temporal Swimming Assays Work Optimally With Fbs Acontrasting
confidence: 38%
See 2 more Smart Citations
“…Brucella broth supported some motility, but a large number of cells were observed to swim only when FBS was present. FBS is known to promote robust H. pylori growth (Testerman et al, 2001), but our data show that it also promotes motility. For this reason, we used FBScontaining medium (BB10) for all further analyses.…”
Section: H Pylori Temporal Swimming Assays Work Optimally With Fbs Acontrasting
confidence: 38%
“…H. pylori requires zinc for growth in vitro (Testerman et al, 2001(Testerman et al, , 2006. We do not know whether zinc is limiting in the stomach, but studies have found that H. pylori infection lowers mucosal zinc concentrations (Sempértegui et al, 2007), possibly due to the presence of neutrophils, which produce the zinc-chelating agent calprotectin (Kehl-Fie & Skaar, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, pellets were re‐suspended in inoculating fluid IF‐0a GN/GP (1.2×), and then supplemented to a final concentration of 0.05% bovine serum albumin (BSA) and 1.25 mmol/L NaHCO 3 . ( H. pylori has been shown to use more carbon sources and grow successfully in media containing BSA,28, 29 so it was included to ensure better visualization of metabolic activity in the VBNC state.) Dye mix D (Biolog) was then added to achieve a final concentration of 0.01%; 100 μL of this solution was pipetted into each well of the PM1 plate, which was then incubated in microaerobic conditions for 48 hours.…”
Section: Methodsmentioning
confidence: 99%
“…This could be attributed partially to the high level of genetic diversity presented by H. pylori strains, which may cause fail of growth in currently available defined media (19).…”
Section: Discussionmentioning
confidence: 99%